Residência universitária para estudantes indígenas na Universidade Federal do Pará - HAMEL, Leila de Fátima Cabral (2023)
This work aims to produce a building within the Federal University of Pará (UFPA) that serves as a residence for indigenous students of UFPA. For this purpose, two research steps were carried out, the first was a bibliographic research on indigenous schools, access and permanence in Higher Education Institutions (HEI), and the second part was related to case studies of university residences, presizing analyzes, program project needs, questionnaire and consultations. The adversities faced by indigenous students, both in admission and permanence, are acknowledged, emphasizing the importance of affirmative policies aimed at the group, as well as support groups within the institution. The presence of these groups within HEI enables a rich cultural exchange for all involved and should be encouraged. The analysis of the proposed building takes place within the parameters defined by UPFA for on-campus buildings, from the point of view of environmental comfort and the fulfillment of the proposed needs program, both by the target audience and by the building typology.